Anaemia in HIV-infected children: severity, types and effect on response to HAART - Nyesigire Ruhinda Eunice; Bajunirwe Francis; Kiwanuka Julius (BMC, 2012)
Abstract Background HIV and anaemia are major health challenges in Africa. Anaemia in HIV-infected individuals is associated with more rapid disease progression and a poorer prognosis if not addressed appropriately. This study aimed at determining the severity and types of anaemia among HIV infected children and its effect on short term response to antiretroviral therapy (ART). Methods At baseline, clinical and haematological parameters of 257 HIV-infected ART-naïve children aged 3 months to 18 years were assessed to determine the prevalence, severity and types of anaemia. ART eligible patients were started on therapy according to WHO criteria, enrolled (n=88) into an observational cohort and followed up for 6 months. Results Anaemia was present in 148/257 (57.6%) of children, including (93/148) 62.2% with mild anaemia, 47/148 (32.0%) moderate anaemia, and 7/148 (4.8%) with severe anaemia. The mean haemoglobin (hb) was lower among children with more advanced HIV disease (p<0.0001). Microcytic-hypochromic anaemia (44.9%) was the commonest type of anaemia. Anaemia was independently associated with young age (p <0.0001), advanced HIV WHO disease stage (p = 0.034) and low CD4 percentage (p = 0.048). The proportion of children who had attained viral suppression (viral load <400 copies/ml) at 3 months was significantly lower among the anaemic children, 31/58 (53.4%) compared to the non-anaemic children 26/30 (86.7%) (p=0.002). However, the difference in clinical and immunological response between the anaemic and non-anaemic patients did not reach statistical significance. Conclusion Anaemia is highly prevalent among HIV-infected children in a rural Ugandan clinic and is associated with poorer virological suppression. However, the anaemia did not impact clinical and immunological response to ART among these children.